Efficiency analysis of dairy buffalo enterprises in Catalca district of Istanbul - Kaygisiz, Ferhan; Evren, Atif; Kocak, Omor; Aksel, Mehmet; Tan, Talat (ANKARA UNIV PRESS, 2018)
The purpose of this study is to determine the efficiencies and economic situations of dairy buffalo enterprises in Catalca district of Istanbul. Research material was collected by means of a questionnaire from 32 enterprises, determined by purposive sampling method in 2013 production periods. According to calculations made per buffalo milked in enterprises, the shares of expenses for feed, labour, veterinary-health, electricity-water, maintenance and repairment, depreciation, general administration and other things in total expenses consist of 54.23%, 25.87%, 1.77%, 2.62%, 1.98%), 10.15%, 2.56% and 0.83% respectively. The average benefit/cost ratio for enterprises was found to be 1.27, whereas the unit cost of milk was 3.31 TL. The measurement of the efficiencies was realized by data envelopment analysis. In this analysis, input and output oriented CCR model with 3 outputs and 5 inputs was adopted. Milk-revenue, calf-revenue and increase in inventory were included in the analysis as outputs and feeding expense, whereas labor-force, veterinary and health expense, depriciation and electricity-water expenses as inputs. At the end, potential improvements that could be advised for inefficient enterprises were determined. The rations of efficient and inefficient enterprises were found 53% and 47% respectively. The factors that affected efficiency score were modeled by regression analysis. Increase in inventory, labor cost were determined to be two influential factors on efficiency (p < 0.05).
Keywords: Dairy buffalo; data envelopment analysis; economic analysis; productivity; technical efficiency; FATTENING ENTERPRISES; PROVINCE; REGION; TURKEY; FARMS; Veterinary Sciences